A simple optimized design of an electrode to conduct flash sintering at room temperature and low onset electric field. (September 2020) - Li, Xiang; Huang, Rongxia; Wang, Xilin; Liu, Guanghua; Jia, Zhidong; Wang, Liming
Abstract: Flash sintering is a fabulous method to sinter ceramics in several seconds at low furnace temperatures.For the first report, with an optimized design of electrodes by introducing extra tips, dry zinc oxide specimens were sintered at room temperature under an Alternating Current (AC) field of 1, 765 V/cm without any aids. The sintering processes could be induced by surface flashover, which was a new mechanism and verified by the experimental results. The method lowers the onset electric field and currents, to prevent the physical fracture of specimens caused by a large power surge when flash events occur. Graphical abstract: With extra tips in electrode, the onset flash sintering electric filed was lower at 1, 765 V/cm and a new mechanism refer to surface flashover was found. Image, graphical abstract